Notary Responsibility for Security Deposit in Sale and Purchase of Land for Investment - Halil, Elsa Aulia; Djumardin, Djumardin; Hirsanuddin, Hirsanuddin (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This research aims to explain the authority of notaries in terms of buying and selling land for investment and analyze the form of notary's responsibility if proven to have committed a criminal act against security deposits in terms of buying and selling land for investment. The research method used is normative legal research, with a statutory approach, conceptual approach and case approach. The results of the research can be concluded that the Notary who receives the deposit money indirectly becomes a party to the deed he makes himself, because a deposit agreement arises between the Notary and the confronters. The deed, which was previously an authentic deed that has perfect evidentiary power, degrades its evidentiary power to become like a deed under the hand. The form of criminal responsibility in the criminal decision of the Mataram High Court Decision Number 1/PID/2023/PT.MTR. which in its opinion upheld the Mataram District Court Decision Number 126/Pid.B/2022/PN.PYA which stated that Defendant I Chuck Wijaya S.H., M.Kn. and Defendant II Lalu Ading Buntaran Alias Lalu Buntaran were legally and convincingly proven guilty of committing a crime as charged by the Public Prosecutor.